Antioxidant and ameliorative effects of selected Nigerian plants on hormonal imbalance associated with dysmenorrhea in albino rats - Ige, Azeezat Bolade; Ogunlakin, Akingbolabo Daniel; Sonibare, Mubo Adeola (Frontiers in Nutrition, 2025)
IntroductionConventional treatments, such as non-steroidal anti-inflammatory drugs (NSAIDs), are widely used for the treatment of dysmenorrhea but are often associated with side effects, necessitating the search for alternative therapies. This study investigates the antioxidant and hormonal effects of selected Nigerian medicinal plants—Aristolochia littoralis, Picralima nitida, Sorghum bicolor, Spondias mombin, and Xylopia aethiopica—traditionally used for dysmenorrhea management.MethodsPhytochemical screening was carried out to confirm the presence of bioactive compounds such as flavonoids, alkaloids, tannins, and phenolic acids. Antioxidant assays, including DPPH, FRAP, and nitric oxide scavenging assays, were conducted to evaluate the free radical scavenging activities of the plant extracts. Additionally, an in vivo study was performed using female Wistar rats to assess the effects of the extracts on key reproductive hormones—luteinizing hormone (LH), follicle-stimulating hormone (FSH), and estradiol (E2)—as well as lipid profiles, including total cholesterol (TC), triglycerides (TG), and high-density lipoprotein (HDL-C).Results and discussionSignificant antioxidant activity of S. bicolor is 69.55 ± 6.96% DPPH inhibition at 1,000 μg/mL. The FRAP assay showed a strong reducing capacity in X. aethiopica is 4.71 ± 0.14 mg/mL. In the NO scavenging assay, P. nitida (186.88 ± 0.78 μM) and S. fistula (190.91 ± 4.38 μM) displayed notable activity. All examined plant extracts have increased estradiol levels significantly compared to the untreated group. Lipid profile analysis showed improved cardiovascular markers, with A. littoralis exhibiting the highest HDL/LDL ratio (1.394 ± 0.014) and X. aethiopica showing the lowest total cholesterol levels (2.276 ± 0.129 mmol/L). The GSH assay further presented S. mombin as having the highest GSH concentration (0.190 ± 0.034 mM), indicating enhanced antioxidant defense. The most active plants regarding the evaluated parameters were S. mombin, S. bicolor, A. littoralis, and X. aethiopica, based on antioxidant, hormonal, and lipid profile assays. These results provide strong pharmacological support for their traditional use in dysmenorrhea management and suggest that they could be valuable in developing plant-based therapies. Future studies should assess additional oxidative markers, explore long-term treatment effects, and work toward the standardization of these medicinal extracts as supplementary therapy for cancers in premenopausal women.